1994
DOI: 10.1002/gcc.2870110304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization, allelic imbalance, and fluorescence in situ hybridization on chromosome 8 in prostate cancer

Abstract: Due to problems with primary tumor cell culture, conventional cytogenetics has yielded little insightful information on chromosomal alterations in prostate cancer. The primary aim of this study was to define the ability of comparative genomic hybridization (CGH) to detect and map genetic deletions in prostate tumors. A secondary aim was to apply multiple assays to individual tumors as a means of deciphering the mechanisms of genetic alterations in prostate cancer. CGH results were compared with allelic imbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(109 citation statements)
references
References 23 publications
7
101
1
Order By: Relevance
“…We have found 50% of prostate tumors showing LOH at one or more 13q markers and no correlation between 13q LOH and DNA ploidy, indicating 13q deletion to be an early, non-random, and independent chromosomal alteration. The frequently deleted region on 13q in these 36 prostate cancers was in agreement with the lost region detected by previous CGH analyses (Cher et al, 1994;Visakorpi et al, 1995). However, in the LOH mapping (Figure 2), two independent smallest regions of overlapping deletions were further de®ned.…”
Section: Discussionsupporting
confidence: 90%
“…We have found 50% of prostate tumors showing LOH at one or more 13q markers and no correlation between 13q LOH and DNA ploidy, indicating 13q deletion to be an early, non-random, and independent chromosomal alteration. The frequently deleted region on 13q in these 36 prostate cancers was in agreement with the lost region detected by previous CGH analyses (Cher et al, 1994;Visakorpi et al, 1995). However, in the LOH mapping (Figure 2), two independent smallest regions of overlapping deletions were further de®ned.…”
Section: Discussionsupporting
confidence: 90%
“…The CGH technique provides informa tion not only on the overall ocurrence of amplifications, but also on the extent of the regions affected [51,[53][54][55], The results obtained are instrum ental in the ultimate id en ti fication and isolation of the genes involved.…”
Section: Recurrent D N a Alterations In Bone A N D Soft T Issu E T U mentioning
confidence: 99%
“…glioma [53,63], nor has it previously been associated w ith the developm ent of hum an sarcomas. Conceivably, the Iq21-q22 region may harbor a gene(s) im portant for h u m an bone and soft tissue tum or initiation and/or progression.…”
Section: Recurrent D N a Alterations In Bone A N D Soft T Issu E T U mentioning
confidence: 99%
“…For example, frequent allelic loss of the LPL gene (8p22) in prostate cancer suggests that a tumor suppressor gene (or genes) is located in this region (7)(8)(9)(10)(11). Likewise, the c-myc gene (8q24) is commonly overrepresented or amplified in advanced and recurrent prostate cancer, suggesting that amplification of this oncogene (or a neighboring gene) may be critical for the progression of this cancer (12)(13)(14). We have recently shown that concurrent overrepresentation of c-myc and loss of LPL independently predicts a poor overall survival and progression-free survival in men with stage pT 3 N 0 M 0 prostate cancer (15).…”
mentioning
confidence: 99%